Treasures of America's national parks. 5, The best of the national parks [videorecording (DVD)]. (Distributed by Questar, 2008)
Discover a universe of the spectacular and seek out the best place to delve deep into the earth, scale a mountain or tie the knot. Witness molten lava bubbling from the earth, catch a spectacular sunrise above the clouds and more.